The witch-hunt, or, The triumph of morality - Bailey, F. G. (Frederick George) (Cornell University Press, 1994)
"In the village of Bisipara in eastern India, an anthropologist is witness to a drama when a young girl takes a fever and quickly dies. The villagers find Susila's death suspicious and fear that she was possessed. Holding an investigation to find someone to blame, they carry out a hurried inquiry because the stage must be cleared for the annual celebration of the birthday of the god Sri Ramchandro. However, they eventually agree on the identity of a culprit and exact from him a large fine." "F. G. Bailey, who was doing fieldwork in Bisipara the 1950s, tells what it was like to be living there during this witch-hunt. As his narrative unfolds, we sense the very texture of the villagers' lives - their caste relationships, occupations, kinship networks, and religious practices. We became familiar with the sights, sounds, and smells of Bisipara and with many of the village men and women. And we learn their ideas of health and disease, their practice of medicine and burial customs, their ways of resolving discord." "The author's commentary opens the curtain on a larger and more complicated scene. It portrays a community in the process of change. From one aspect the offender is seen as a heroic individual who has broken from the chains of the past, a dissenter standing up for his rights against an entrenched and conservative establishment. From the opposite point of view he is a troublemaker who rejects the moral order on which society and the good life depend, a man who has trespassed outside his proper domain. From Bailey's neutral perspective, the offender's conduct threatened those in power; their determined and successful effort to punish him was an attempt to protect their own privileged position. In doing so, of course, they could say they were defending the moral order of their community."